Sufism and Politics in Modern Egypt: A Study of Azmiyyah Sufi Order in Alexandria - Dzawafi, Agus Ali; Alif, Muhammad (Aqlania, 2024)
The Azmiyyah Sufi Order, also known as the Azmiyyah Tariqa, has played a significant role in the spiritual and social landscape of Egypt, particularly during the Ottoman and modern periods. Emerging from the rich tapestry of Sufi traditions, the Azmiyyah Order is characterized by its unique practices, teachings, and its relationship with the socio-political dynamics of Egypt. This synthesis will explore the historical development, key figures, and contemporary relevance of the Azmiyyah Sufi Order in Egypt, drawing on a variety of scholarly sources. Throughout the Ottoman period, the Azmiyyah Order, like other Sufi orders, navigated the complex interplay between spirituality and politics. The political elite often sponsored Sufi rituals and gatherings as a means of consolidating power and countering the influence of more radical Islamist movements. This relationship between Sufism and the state was particularly evident during the 19th century, when Sufi orders, including the Azmiyyah, became involved in the socio-political fabric of Egypt, often aligning themselves with the ruling authorities to maintain their status and influence. The Azmiyyah Order's ability to adapt to changing political landscapes has been a key factor in its longevity and relevance.